2010
DOI: 10.1097/mao.0b013e3181e3deb2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Romberg Testing Does Not Detect Vestibular Disease

Abstract: The tandem Romberg and tandem walking tests, despite being in widespread clinical use as office screening tests, may not be effective at determining the presence of newly developed vestibular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…Therefore the clinician should use this test with caution, and perhaps only as an adjunct to other tests. Thus we agree with Longridge and Mallinson [15] that tandem walking with eyes closed is not useful in screening patients for vestibular disease, when the dependent measure is the number of steps taken. Despite it’s long history, high reliability, and widespread use this test is so challenging for some normals or so easy for some known patients that it does not differentiate normals from patient groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore the clinician should use this test with caution, and perhaps only as an adjunct to other tests. Thus we agree with Longridge and Mallinson [15] that tandem walking with eyes closed is not useful in screening patients for vestibular disease, when the dependent measure is the number of steps taken. Despite it’s long history, high reliability, and widespread use this test is so challenging for some normals or so easy for some known patients that it does not differentiate normals from patient groups.…”
Section: Discussionsupporting
confidence: 91%
“…Although TW is widely used, Longridge and Mallinson recently reported that less than 30% of patients or normals could perform 5 steps of tandem walking with eyes closed [15]. Kammerlind et al [13] tested TW for 15 steps with eyes open and showed that patients as well as normals could perform a mean of 13 consecutive steps, but they did not test the eyes closed condition.…”
Section: Introductionmentioning
confidence: 99%
“…(11) Longridge and Mallinson recently reported that less than 30% of patients with vestibular disorders or normals could perform 5 steps of tandem walking with eyes closed. (13) Patients with vestibular impairments have impaired performance compared to normals. (14) Performance on several variations of TW declines slightly with age.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, postural stability in healthy young subjects was assessed by using only eyes open, eyes closed, or sway-referenced vision. Such conditions have been too easy, so the upper limit of stability was never reached (6). With the visual perturbation, we have a full range of perturbation from absolute stability to fall in perfectly healthy young subjects.…”
Section: Introductionmentioning
confidence: 99%